The role of root and tuber crops in strengthening agri‐food system resilience in Asia. A literature review and selective stakeholder assessment. - Prain, Gordon; Naziri, D. (International Potato Center, 2020)
This publication begins with a review of the literature on resilience, noting the wide diversity of perspectives on the term and the range of disciplines that have employed the concept. From its use to describe engineering systems that are close to equilibrium, the concept of resilience has evolved to characterize non‐linear systems far from equilibrium in ecology and later, in social‐ecological systems where resilience derives from the complex interactions of ecosystems and social systems. It then looks in some detail at the way the term resilience has been used more recently in relation to recovery from disaster and in assuring food and nutrition security. Drawing on this literature, and also on earlier food security work by the Food Security Through Asian Root and Tuber Crops project (FoodSTART), a provisional conceptual framework was proposed to help understand the relationship between shocks and stressors and the social‐ecological system.